The Implementation of the Fruit Battery Assisted Inquiry Model to Improve Fifth Grade Students’ Understanding of Science Concepts at SD IT Muhammadiyah 06 Lhokseumawe - Asywaq Fadilah (Jurnal Pendidikan Fisika dan Sains, 2025)
This study was motivated by the low levels of student engagement and conceptual understanding of science among fifth- grade students at SD IT Muhammadiyah 06 Lhokseumawe regarding simple electrical circuits, due to a teaching approach that tends to be theoretical. This Classroom Action Research (CAR) aims to improve the quality of the learning process and student outcomes through the application of a guided inquiry model supported by lemon bio-batteries. The research subjects consisted of 24 students. Data were collected through observations of teacher and student activities as well as written tests at the end of each cycle. The results showed a significant improvement in the quality of the learning process, with teacher activities and student engagement reaching 100% (Excellent) in Cycle II. This improvement had a linear impact on learning outcomes, marked by an increase in the class average score from 77.92 (Cycle I) to 86.67 (Cycle II). The class passing rate surged dramatically from 66.67% to 91.67%, thus exceeding the success target (≥80%). In conclusion, the guided inquiry model using lemon batteries proved effective in optimizing student engagement while ensuring their conceptual understanding of IPAS.